Regenerative Endodontic: Cell-Based Versus Cell-Free Approach - Ruangsawasdi, Nisarat; Kaewprag, Jittranan (Mahidol Dental Journal, 2018)
In regenerative endodontics, the cell-based and cell-free approach in immature permanent teeth is a novel root canal treatment that attempts to regenerate a functional pulp rather than a mere prosthetic material in the root canal system. However, the outcomes of this treatment are still uncertain as they depend on various factors. Accordingly, there is a need for better understanding the biology behind pulp regeneration as well as an improving tissue ingrowth into the pulp space. This review will focus on the update horizon of alternative approaches in regenerative endodontic and provide the insight into the account of pulp tissue engineering.